Hb lepore/β0-thalassaemia with α+-thalassaemia interactions, a potential diagnostic pitfall - Hafiza, Alauddin; Suziana, Mohamad Nasir; Madzlifah, Ahadon; Raja Zahratul Azma, Raja Azma; Azlin, Ithnin; Noor Hamidah, Hamidah; Hamidah, B. Alias; Loh, C. Khai; Zarina, Abdul-Latiff; Nor Azian, Abdul Murad; Ainoon, Othman (Malaysian Society of Pathologists, 2015)
Haemoglobin (Hb) Lepore is a variant Hb consisting of two α-globin and two δβ-globin chains. In a heterozygote, it is associated with clinical findings of thalassaemia minor, but interactions with other haemoglobinopathies can lead to various clinical phenotypes and pose diagnostic challenges. We reported a pair of siblings from a Malay family, who presented with pallor and hepatosplenomegaly at the ages of 21 months and 14 months old. The red cell indices and peripheral blood smears of both patients showed features of thalassaemia intermedia. Other laboratory investigations of the patients showed conflicting results. However, laboratory investigation results of the parents had led to a presumptive diagnosis of compound heterozygote Hb Lepore/β-thalassaemia and co-inheritance α+-thalassaemia (-α3.7). Hb Lepore has rarely been detected in Southeast Asian countries, particularly in Malaysia. These two cases highlight the importance of family studies for accurate diagnosis, hence appropriate clinical management and genetic counseling